Financial Risk Mitigation for Gayo Coffee Processors : Interventions in Financial Management and Business Legal - Hafizhah Risnafitri; Adella Yuana; Noer Octaviana Maliza; Rahma Aliya; Murlida Murlida; Dara Angreka Soufyan (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to mitigate financial risks faced by Gayo Arabica coffee processors through interventions in financial management capacity building and the strengthening of business legality. The program was implemented using a three-stage approach consisting of socialization, hands-on assistance and practical training, and evaluation. A total of ten members of the partner group participated in the program, with activities focused on identifying operational costs, preparing simple financial statements, and drafting basic sales and purchase contracts. Data were analyzed using a mixed-methods approach, integrating quantitative and qualitative techniques to evaluate the program’s effectiveness. The results, evaluated through pre- and post-test assessments, indicate a significant increase in participants’ capacity. In the financial aspect, a paradigm shift was observed from a lack of cost awareness to improved cost consciousness, with 100% of participants demonstrating an understanding of the importance of financial record-keeping. In terms of business legality, all partners (100%), exceeding the initial target of 60%, were able to draft simple written sales contracts. Overall, the program effectively reduced financial risks by strengthening partners’ bargaining power, providing greater income certainty, and enhancing business professionalism through the application of structured financial management practices and formal legal contracts.